Non-Timber Forest Products in Cat Tien: Local Use and Sustainable Management - Thanh Sang Dinh; Thi Van Pham (Jurnal Manajemen Hutan Tropika, 2023)
Rural ethnic minority groups in Cat Tien National Park (CTNP) have relied heavily on non-timber forest products (NTFPs) and threatened its natural forest environment. Still, the real context of the NTFP consumption between indigenous peoples (IPs) and migrant ethnic minority group (MEs) has been poorly comprehended. Also, the participatory rural appraisal (PRA) and the “walk-in-the-wood” method were applied to analyse the NTFP consumption between these IPs and these MEs. The study results indicated that the two local groups had a high or a relatively high dependence on the NTFPs and there was a shifting trend from subsistence to cash income (p-value = 0.000 < 0.05). Also, these IPs had a better knowledge about edible forest plants than these MEs, whilst various more MEs consumed forest fauna for medicinal demand. These MEs harvested and consumed those NTFPs more intensively, but these IPs did the resources for more self-consumption related to the indigenous traditions. Based on the local context, NTFP use patterns, cultural dissimilarity, and local capacity empowerment remain needed in park administration strategies. Similarly, culture-based arrangements would contribute to positive outcomes and sustainable management of the park.